CIRCADIAN RHYTHM DISRUPTION: CIRCADIAN RHYTHM ABNORMALITIES AND THEIR IMPACT ON STUDENTS - Gaffarova, Sevinj; Rahmat, Awni; Jamil, Ilhami; Wan Othman, Wan Nur Balqis; Mohammad Yazid, Nuratiqah; Khairil Azli, Syaheera Noor; Che Mohd Nassir, Che Mohd Nasril; Ahmed, Mohamed Ayaaz; Md Tajudin, Huriyyah Hamiemah; Jaffer, Usman (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2025)
Circadian rhythm abnormalities disrupt the 24-hour biological cycle, affecting sleep, wakefulness, and other physiological functions. These disruptions are increasingly common among students due to irregular sleep schedules, academic pressures, and lifestyle factors. This study examines the prevalence of circadian rhythm abnormalities among students and their impact on daily functioning, academic performance, and mental well-being. A systematic review of articles published within the last five years, and selected based on specific inclusion of criteria relevant to student populations, and a primary focus on circadian disruptions. The literature review highlights the negative effects of circadian rhythm abnormalities, such as poor sleep quality, increased stress, anxiety, and depression, which significantly impair students’ academic success and mental health. Effective interventions like sleep hygiene practices, reducing screen time, and public health education are proposed to address these issues. From an Islamic perspective, the Quran emphasizes the balance of day and night (verse 28:73), with night for rest and day for productivity. Islamic teachings support practices like Qailullah (mid-day nap) and Tahajjud (night prayer), which align with circadian principles and have been linked to better mental health and overall well-being. This study highlights the importance of integrating scientific and spiritual approaches to mitigate circadian rhythm disruptions and promote holistic well-being.